![]() | 1 | initial version |
Let f(x)=log(tang(x)), with g(x)=π2tanhx It can be seen that f is a differentiable function in (0,+∞), so it makes sense to try to compute lim To this end, we first obtain f' by applying the chain rule: f'(x)=\frac{1}{\tan g(x)} \frac{1}{\cos^2 g(x)}g'(x), where g'(x)=\frac{\pi}{2}\frac{1}{\cosh^2 x}. By using some trigonometric relations, we get \tan g(x)\,\cos^2 g(x)=\sin g(x)\cos g(x)=\frac{1}{2}\sin 2g(x). Hence, f'(x)=\frac{2g'(x)}{\sin2g(x)}. SageMath can handle the limit of the above expression of f':
sage: g(x) = (pi/2) * tanh(x)
sage: gp = g.derivative()
sage: limit(2*gp(x)/sin(2*g(x)), x=+oo)
2
Consequently, \lim_{x\to+\infty}f'(x)=2, as conjectured by @Emmanuel Charpentier in his comment.
It is not hard to finish the computation by hand. Since \lim_{x\to+\infty}2g(x)=\pi \lim_{x\to+\infty}\tanh x=\pi, we have the following equivalence as x\to+\infty: \sin 2g(x)=\sin(\pi-2g(x))=\sin\pi(1-\tanh x)\sim \pi(1-\tanh x). Therefore, \begin{aligned} \lim_{x\to+\infty}f'(x) &=\lim_{x\to+\infty}\frac{2g'(x)}{\sin2g(x)} \\ &=\lim_{x\to+\infty}\frac{\pi/\cosh^2x}{\pi(1-\tanh x)} \\ &=\lim_{x\to+\infty}\frac{1}{(\cosh x-\sinh x)\cosh x} \\ &=\lim_{x\to+\infty}\frac{2}{e^{-x}(e^x+e^{-x})} \\ &=\lim_{x\to+\infty}\frac{2}{1+e^{-2x}} =2. \end{aligned}
![]() | 2 | No.2 Revision |
Let
f(x)=\log(\tan g(x)),
with
$$
g(x)=\frac{\pi}{2}\tanh x
x.
It can be seen that $f$ is a differentiable function in $(0,+\infty)$, so it makes sense to try to compute
\lim_{x\to+\infty}f'(x).
To this end, we first obtain $f'$ by applying the chain rule:
f'(x)=\frac{1}{\tan g(x)} \frac{1}{\cos^2 g(x)}g'(x),
where
g'(x)=\frac{\pi}{2}\frac{1}{\cosh^2 x}.
By using some trigonometric relations, we get
\tan g(x)\,\cos^2 g(x)=\sin g(x)\cos g(x)=\frac{1}{2}\sin 2g(x).
Hence,
f'(x)=\frac{2g'(x)}{\sin2g(x)}.
$$
SageMath can handle the limit of the above expression of $f'$:
sage: g(x) = (pi/2) * tanh(x)
sage: gp = g.derivative()
sage: limit(2*gp(x)/sin(2*g(x)), x=+oo)
2
Consequently, \lim_{x\to+\infty}f'(x)=2, as shown in part of the results shown in the opening post or conjectured by @Emmanuel Charpentier in his comment.
It is not hard to finish the computation by hand. Since \lim_{x\to+\infty}2g(x)=\pi \lim_{x\to+\infty}\tanh x=\pi, we have the following equivalence as x\to+\infty: \sin 2g(x)=\sin(\pi-2g(x))=\sin\pi(1-\tanh x)\sim \pi(1-\tanh x). Therefore, \begin{aligned} \lim_{x\to+\infty}f'(x) &=\lim_{x\to+\infty}\frac{2g'(x)}{\sin2g(x)} \\ &=\lim_{x\to+\infty}\frac{\pi/\cosh^2x}{\pi(1-\tanh x)} \\ &=\lim_{x\to+\infty}\frac{1}{(\cosh x-\sinh x)\cosh x} \\ &=\lim_{x\to+\infty}\frac{2}{e^{-x}(e^x+e^{-x})} \\ &=\lim_{x\to+\infty}\frac{2}{1+e^{-2x}} =2. \end{aligned}
![]() | 3 | No.3 Revision |
Let f(x)=\log(\tan g(x)), with g(x)=\frac{\pi}{2}\tanh x. It can be seen that f is a differentiable function in (0,+\infty), so it makes sense to try to compute \lim_{x\to+\infty}f'(x). To this end, we first obtain f' by applying the chain rule: f'(x)=\frac{1}{\tan g(x)} \frac{1}{\cos^2 g(x)}g'(x), where g'(x)=\frac{\pi}{2}\frac{1}{\cosh^2 x}. By using some trigonometric relations, we get \tan g(x)\,\cos^2 g(x)=\sin g(x)\cos g(x)=\frac{1}{2}\sin 2g(x). Hence, f'(x)=\frac{2g'(x)}{\sin2g(x)}. SageMath can handle the limit of the above expression of f':
sage: g(x) = (pi/2) * tanh(x)
sage: gp = g.derivative()
sage: limit(2*gp(x)/sin(2*g(x)), x=+oo)
2
Consequently,
\lim_{x\to+\infty}f'(x)=2,
as shown in part of the results shown reported in the opening post or conjectured by @Emmanuel Charpentier in his comment.
It is not hard to finish the computation by hand. Since \lim_{x\to+\infty}2g(x)=\pi \lim_{x\to+\infty}\tanh x=\pi, we have the following equivalence as x\to+\infty: \sin 2g(x)=\sin(\pi-2g(x))=\sin\pi(1-\tanh x)\sim \pi(1-\tanh x). Therefore, \begin{aligned} \lim_{x\to+\infty}f'(x) &=\lim_{x\to+\infty}\frac{2g'(x)}{\sin2g(x)} \\ &=\lim_{x\to+\infty}\frac{\pi/\cosh^2x}{\pi(1-\tanh x)} \\ &=\lim_{x\to+\infty}\frac{1}{(\cosh x-\sinh x)\cosh x} \\ &=\lim_{x\to+\infty}\frac{2}{e^{-x}(e^x+e^{-x})} \\ &=\lim_{x\to+\infty}\frac{2}{1+e^{-2x}} =2. \end{aligned}